Borrowing from our foremothers : reexamining the women's movement through material culture, 1848-2017 - Forss, Amy Helene (University of Nebraska Press, 2021)
Borrowing from Our Foremothers offers a panorama of women's struggles through artifacts to establish connections between the generations of women's right activists. In a thorough historical retelling of the women's movement from 1848 to 2017, Amy Helene Forss focuses on items borrowed from our innovative foremothers, including cartes de visite, clothing, gavels, sculptures, urns, service pins, and torches. Framing the material culture items within each era's campaigns yields a wider understanding of the women's metanarrative. Studded with relics and ninety-nine oral histories from such women as Rosalynn Carter to Pussyhat Project cocreator Krista Suh, this book contributes an important and illuminating analysis necessary for understanding the development of feminism as well as our current moment. -- Provided by publisher